Effects of fermented feed on growth performance, serum biochemical indexes, antioxidant capacity, and intestinal health of lion-head goslings - Fu, Zhiqi; Ao, Na; Liang, Xiaoen; Chen, Jinhuang; Wang, Yuchuan; Wang, Qing; Fu, Jing; Liu, Chunpeng; Lu, Lizhi (Frontiers in Veterinary Science, 2023)
We really appreciate for editor and reviewers' warm work earnestly. Our manuscript entitled "Effects of fermented feed on growth performance, serum biochemical indexes, antioxidant capacity and intestinal health of lion-head goslings" has been revised in response to the reviewers' comments, and resubmitted. Thank you for the opportunity to resubmit this manuscript for possible publication in "frontiers in veterinary science". We have given serious consideration to the all reviewers' comments and suggestions, and have revised the manuscript as appropriate. The two reviewers provided many valuable insights for us, sincerely thank you again. We would be glad to respond to any further questions and comments that you may have.Sincerely,